Seidman's Legislative History of Excess Profits (Book). - Smith, Frank P.; Mason, Perry (The Accounting Review, 1949)
Abstract Reviews the book "Seidman's Legislative History of Excess Profits Tax Laws 1946-1947," by J.S.Seidman.